2021
DOI: 10.1177/02692163211005343
|View full text |Cite
|
Sign up to set email alerts
|

Gamification for promoting advance care planning: A mixed-method systematic review and meta-analysis

Abstract: Background: Gamification has been adopted in the health care field for broaching sensitive topics and increasing motivation for behavior changes. Games developed to stimulate discussion surrounding end-of-life issues, and thereby promoting advance care planning also emerged. Aim: The aim is to integrate the quantitative evidence and qualitative evidence to understand the effectiveness of and experience with games for advance care planning. Design: A mixed-methods systematic review and meta-analysis (PROSPERO I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…This is because there could be differences in the regional and medical environments within Japan. Second, further reliability and validity testing is needed to make this list useful for scale development because this list was developed as a support tool to stimulate ACP communication as in other countries (Delgado-Guay et al, 2016; Li et al, 2021; Liu et al, 2021; Menkin, 2007). The third is the inability to capture changes in preferences because of the cross-sectional nature of the study.…”
Section: Discussionmentioning
confidence: 99%
“…This is because there could be differences in the regional and medical environments within Japan. Second, further reliability and validity testing is needed to make this list useful for scale development because this list was developed as a support tool to stimulate ACP communication as in other countries (Delgado-Guay et al, 2016; Li et al, 2021; Liu et al, 2021; Menkin, 2007). The third is the inability to capture changes in preferences because of the cross-sectional nature of the study.…”
Section: Discussionmentioning
confidence: 99%
“…44 The Hello game is an inexpensive and easily disseminated intervention, recommended for those aged 13 years or older, that promotes ACP through gamification. 17,45,46 It does this by integrating ACP with an enjoyable game to overcome reluctance to discussing death and dying and introducing open-ended questions to prompt in-depth discussions of values and preferences about EOLC. 47 It can also increase the confidence of healthprofessionals to have these conversations.…”
Section: Communication Support Interventions and Toolsmentioning
confidence: 99%
“…The gamified element was designed to facilitate the discussion on sensitive topics (van Gaalen et al, 2020). This approach proved to be successful in creating behavioural changes in sensitive topics within non-game environments (Liu et al, 2021).…”
Section: Life Unlocking Card Game (Kem Phi K Hi Ch ıWit) Overviewmentioning
confidence: 99%
“…Previous research has shown that ACP could improve patient outcomes, increase family communication and satisfaction with care, and reduce unnecessary hospitalization (Borgstrom, 2020;Kernick et al, 2018;van Wijmen, Pasman, Twisk, Widdershoven, & Onwuteaka-Philipsen, 2018). Still, despite several benefits, initiating the ACP and discussing its process is still challenging due to sociocultural and policy barriers that vary between countries (Phenwan et al, 2020), especially since many cultures view death and dying as taboo (Liu et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation